IMPLEMENTASI SISTEM PENANGGULANGAN KEBAKARAN DI UPT PERPUSTAKAAN UNIVERSITAS DIPONEGORO SEMARANG TAHUN 2016 - Ben Vivi Ditria Turnip; Bina Kurnaiwan; Suroto Suroto (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Fire is a matter which may effect problems towards people, utensil of production, process of production, and pollution to environment. Especially related to the huge fire can totally influence the process of production, related to this facts, a system of fire prevention is needed. The significance of the study is to find out the effect of implementing the fire prevention system in UPT Library Diponegoro University Semarang 2016 to propose a concept (program and concept) of the implementation of fire prevention system based on a standardized rules. The methodology used in this research was descriptive qualitative which was the approach of cross observational section. The place of this research was in UPT Library Diponegoro University Semarang. Source of primary data was gained through some qualified interviews by using questionnaire. The data analysis used in this researc was inductive analysis which was a method or a process of deciding a conclusion based on genetal case of circumstances. The result of this research shows that there is no implementation of fire prevention system in UPT Library Diponegoro University Semarang 2016. The central point of the fire can happen was caused by the instalation of electricity problem and flammable material. The means of fire prevention which is available only the fire extinguisher. The fire extinguisher is such kinds of dry chemical and halon that do not yet fit or meet the applicable standards. While the means of rescuing and the fire prevention unit which are not available. The concept given is more like a granted completeness availability in every floor of the building and also the completeness of hydrant and sprinkler. The completeness of manual call point, completeness of means of rescuing unit and composing fire prevention unit